Recurrent bowel necrosis from non-occlusive mesenteric ischemia induced by diabetes ketoacidosis in an adult patient causing mortality: a rare cause of mortality associated with poorly controlled diabetes in adults - Silva, Munasinghe; Gounder, Vinay (International Surgery Journal, 2022)
Diabetes ketoacidosis (DKA) is associated with severe dehydration resulting in non-obstructive mesenteric ischemia (NOMI), which can contribute to severe patient complications. Recurrent episodes of NOMI with DKA in adults can be associated with mortality rarely. We presented a case of an adult patient with poorly controlled insulin-dependent type 2 diabetes mellitus due to poor socioeconomic background who presented to the emergency department with multiple episodes of bowel necrosis causing mortality.